Character Education Values in the Novel Sanggarguri for High School Literature Learning: Nilai Pendidikan Karakter dalam Novel Sanggarguri untuk Pembelajaran Sastra di SMA - Fazlina, Sri Ayu; Saharudin; Aswandikari; Sirulhaq, Ahmad; Burhanudin; Mahyudi, Johan (Universitas Muhammadiyah Sidoarjo, 2026)
Background: Character education is a fundamental component of formal education, particularly in addressing moral and social challenges among students in contemporary society. Specific background: Literary texts grounded in local culture provide concrete representations of character values through narratives, traditions, and social interactions, as reflected in the novel Sanggarguri by Lalu Agus Fathurrahman. Knowledge gap: Previous studies on Sanggarguri have largely emphasized cultural and symbolic dimensions, while systematic analysis of character education values in relation to high school literature learning remains limited. Aims: This study aims to identify character education values embedded in the novel Sanggarguri and to describe their use within high school literature learning. Results: The analysis reveals five dominant values: respect, responsibility, tolerance, cooperation, and courage, manifested through characters’ attitudes, cultural rituals, and moral decision-making. Novelty: This study positions Sanggarguri as a local literary text that integrates Sasak cultural wisdom with character education values. Implications: The findings support the use of local novels as contextual teaching materials for high school literature learning, particularly in developing moral awareness, empathy, and cultural understanding in line with curriculum objectives. Highlights Identification of five core character education values in Sanggarguri. Representation of Sasak local wisdom through literary narratives and traditions. Suitability of the novel for high school literature learning contexts. Keywords Character Education, Novel Sanggarguri, Sasak Culture, High School Literature Learning, Local Wisdom